Blending of collaborative and active learning instructional methods to improve academic performance and self-motivation of vocational students - Ruijuan, Li; Srikhoa, Sarit; Jantharajit, Nirat (Asian Journal of Education and Training, 2023)
This study delves into the integration of collaborative and active learning methodologies as a means to enhance both academic achievement and self-motivation among students in the realm of vocational education. Collaborative learning, with its emphasis on teamwork, problem-solving, and social responsibility, complements the active learning approach, which fosters autonomy, deep understanding, and critical thinking. Together, these strategies form a comprehensive framework that not only facilitates academic excellence but also cultivates the lifelong learning skills imperative for sustained career success. While the potential benefits of collaborative and active learning are evident, the study acknowledges the existence of practical challenges, including limited resources and resistance from educators. Addressing these challenges is paramount for the effective implementation of these pedagogical approaches. Overcoming such obstacles will empower vocational education to harness the transformative potential of collaboration and active learning, equipping students with the necessary skills and motivation to thrive in their chosen careers. By navigating these challenges successfully, educators and institutions can create an environment that prepares students not only for the demands of their immediate professions but also for the dynamic challenges of the evolving professional landscape.